Sag Harbor Civil War Monument - Jackson Benson:::Creator::::::::::::
The Civil War monument at the corner of Madison Street/Sagg Road and Main Street in Sag Harbor, New York. This was Elm Street and High Street in 'New Baytown' in The Winter of Our Discontent. Sign on the fence in the foreground reads "New York" with an arrow pointing right.